2016
DOI: 10.1002/ijc.29982
|View full text |Cite
|
Sign up to set email alerts
|

Beyond a tumor suppressor: Soluble E‐cadherin promotes the progression of cancer

Abstract: E-cadherin (E-cad) plays important roles in tumorigenesis as well as in tumor progression, invasion and metastasis. This protein exists in two forms: a membrane-tethered form and a soluble form. Full-length E-cad is membrane tethered. As a type I transmembrane glycoprotein, E-cad mainly mediates adherens junctions between cells and is involved in maintaining the normal structure of epithelial tissues. Soluble E-cad (sE-cad) is the extracellular fragment of the protein that is cleaved from the membrane after pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
1
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 90 publications
4
95
1
7
Order By: Relevance
“…3C and SI Appendix, Fig. S4A) and notably, 6 of these genes (ARNTL, CEACAM7, GATA2, HHEX, KLRG1, and OGN) have been reported to possess tumor suppressor activity (18)(19)(20)(21)(22)(23). qPCR analysis of the 10 genes in three additional breast cancer cell lines revealed that their expression was down-regulated in hypoxia in a similar manner to that observed in MCF7 breast cancer cells (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 59%
“…3C and SI Appendix, Fig. S4A) and notably, 6 of these genes (ARNTL, CEACAM7, GATA2, HHEX, KLRG1, and OGN) have been reported to possess tumor suppressor activity (18)(19)(20)(21)(22)(23). qPCR analysis of the 10 genes in three additional breast cancer cell lines revealed that their expression was down-regulated in hypoxia in a similar manner to that observed in MCF7 breast cancer cells (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 59%
“…On the other hand, (i) ACTA2 which has been related to increased cell motility in breast cancer and other cancer types (50, 51), (ii) POSTN , a protein secreted by cancer cells that has been described to facilitate cell motility and was recently purposed as an interesting target for prevention and treatment of breast tumor metastasis (52, 53), and (iii) VCAN , known to enhance tumorigenesis and cell mobility, invasion, and survival of breast tumors (54), are all dramatically silenced in IF1-overexpressing breast cancer cells. Besides, we found that IF1 overexpression increased the presence of the epithelial marker E-cadherin involved in maintenance of cell and epithelial tissue integrity and inversely correlated with invasion and metastasis (55, 56). Furthermore, integrin β1 an adhesion molecule (55) related to migration, extravasation, and metastasis (44) is found significantly reduced in IF1-cells.…”
Section: Discussionmentioning
confidence: 79%
“…15, 22 The study presented here identifies a gene signature composed of the TGFβ signaling pathway and EMT genes under the control of CdGAP in ErbB2-expressing breast cancer cells. We demonstrate that CdGAP acts as a novel co-transcriptional repressor with Zeb2 to suppress E-cadherin expression in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%